2019
DOI: 10.1177/0363546519894567
|View full text |Cite
|
Sign up to set email alerts
|

Upper Extremity and Hip Range of Motion Changes Throughout a Season in Professional Baseball Players

Abstract: Background: Loss of upper and lower extremity range of motion (ROM) is a significant risk factor for injuries in professional baseball players. Purpose/Hypothesis: The purpose was to determine changes in ROM in professional baseball players over the course of a single season and their careers. We hypothesized that pitchers and position players would lose ROM, specifically total shoulder motion (total ROM [TROM]) and hip internal rotation (IR), over the course of a season and their careers. Study Design: Case s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…124 Furthermore, significant decreases in range of motion are common, especially in the shoulder, towards the end of the season. 124,125 Therefore, to protect from injury or time lost, baseball athletes need to maintain optimal strength without adversely affecting performance or tissue quality. BFR has been shown to improve strength, endurance, and lean mass about the upper extremity with relatively low loads which would be particularly helpful for the baseball athlete.…”
Section: Injury Prevention and Recoverymentioning
confidence: 99%
“…124 Furthermore, significant decreases in range of motion are common, especially in the shoulder, towards the end of the season. 124,125 Therefore, to protect from injury or time lost, baseball athletes need to maintain optimal strength without adversely affecting performance or tissue quality. BFR has been shown to improve strength, endurance, and lean mass about the upper extremity with relatively low loads which would be particularly helpful for the baseball athlete.…”
Section: Injury Prevention and Recoverymentioning
confidence: 99%
“…Thus, potential changes in hip, knee and ankle ROMs over the course of the in-season phase were not monitored. In this sense, previous study analyzing changes in ADF KF and hip (HIR and HER) ROMs over the course of a competitive season for professional male football ( Moreno-Pérez et al, 2020 ) and baseball ( Camp et al, 2018 ; Chan et al, 2020 ) players, respectively, reported statistically significant ( p < 0.05) decreases in ADF KF and HER ROMs from pre-season to post-season. Although these documented changes in ADF KF and HER ROMs were defined as statistically significant, their magnitudes (approximately 3° and 6° for ADF KF and HER, respectively) may be considered as not relevant from a clinical standpoint as they did not exceed the value of 1.5 times (80–90% of certainty) the magnitudes of the standard error of the measurement (SEM) reported in previously published reliability studies ( Gómez-Jiménez et al, 2015 ; Gradoz et al, 2018 ).…”
Section: Discussionmentioning
confidence: 85%
“…While previous studies have focused on workload, pitch velocity, shoulder range of motion, and other individual factors, there are no data surrounding weather or game variables and injury risk. 6,8,21,35,37 The authors' hypotheses were incorrect, as colder temperatures and longer game durations were not significant risk factors for injury.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have focused on workload, pitch velocity, shoulder range of motion, and other individual factors, there are no data surrounding weather or game variables and injury risk. 6,8,21,35,37…”
Section: Discussionmentioning
confidence: 99%